Gender analysis in empowering women-headed family in Mojosongo Village, Surakarta - Husna, Irma Maulidatul (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2021)
This paper discusses the achievement for the level of equality in the women-headed family empowerment program in Kelurahan Mojosongo, Surakarta City. A woman is one of the population groups that are sustainable to poverty. Women experiencing poverty are women who become the head of the family. In Surakarta City, there are 11.502 women-headed families with a low welfare level. To resolve this problem, the Office of Women's Empowerment, Child Protection, and Community Empowerment (PPPAPM) of Surakarta made an innovation program by forming the Pekka (Women-Headed Family Empowerment) Forum in five poverty-stricken villages, one of which is Mojosongo. Kelurahan Mojosongo is a village that has the highest number of women-headed families, namely 727 people from five poverty-stricken villages. This study used gender analysis of the Longwe model to see the level of equality on women-headed family empowerment in Mojosongo, Surakarta City. The method used in this study was qualitative descriptive, and the data collection was obtained by observations, interviews, and documentation. The results of the study show that the level of equality in the women-headed family in Mojosongo only reached the second stage, namely access. Meanwhile, in the stages of awareness, participation and control have not been achieved. There are two implications of this study, namely practical and theoretical implications. For practical implications, the Surakarta City Government can use it as recommendations for empowerment programs, especially the women-headed family empowerment. The theoretical implications are expected to add to the research literature on gender analysis of the Longwe model in women's empowerment.